OBTAINING FLAVONOID FROM TARAXACUM KOK-SAGHYZ RODIN PLANT GROWING IN KAZAKHSTAN - K.S. Smailova; G.E. Azimbaeva; A.A. Bakibaev; M.S. Abdikerim (Academic Scientific Journal of Chemistry, 2021)
In recent years, the interest of researchers in the herbal preparation has grown significantly. Plants are sources of biologically active substances (BAS). In previous articles, the chemical composition and biologically active substances of plants endemic Taraxacum kok-saghyz Rodin growing in Kazakhstan has been studied. Among the BAS of plant origin, inulin and flavonoids occupy a special place. The article examines the release of inulin and flavonoid from the stem of Taraxacum kok-saghyz Rodin plants. In order to isolate a flavonoid, you first need to extract inulin. Due to the fact that in our plants, inulin accumulates up to 40%. Therefore, the first stage was to isolate inulin: with extractions 1:10 with distilled water for 60 minutes, and in the second stage, the further isolation of the residue was first dried, the dry residue was 1:10 with a ratio of 70% ethanol for 3 hours. The inulin yield was - 5%, the melting point was 1300C. A The yield of flavanoid is 0.66%, the melting point is 1700 C, the aggregate state is acicular light brown light. The structure of the isolated flavonoid was determined on a Uviline 9100 spectrophotometer; the highest absorption was observed at a wavelength of 364 nm. Consequently, the structure of the isolated flavonoid coincides with the literature data. The maxima of the UV, IR, 13С -NMR. spectrum show that flavonol is a derivative